Deteksi Pengendalian Internal Sistem Informasi Akuntansi Penggajian Karyawan Padatoko Langgeng Melalui Audit Kepatuhan - Rizka Maya Shova; Novita Rahmawati; Tri Ratnawati (Manajemen Kreatif Jurnal, 2023)
This article discusses the detection of internal control in the employee payroll accounting information system at Toko Langgeng This research aims to find out the Employee Payroll Flow Chart chart, find out the systems and procedures used in Employee Payroll, Audit compliance with payroll policies and procedures This research uses Descriptive qualitative with Participant observation and field study assistance. The data source used is Primary Data. Data collection is done through direct observation of payroll procedures and internal controls carried out. From this research is expected to provide information about the Payroll system and procedures at Informant